2022
DOI: 10.3389/fimmu.2022.973762
|View full text |Cite|
|
Sign up to set email alerts
|

Marek’s disease virus-specific T cells proliferate, express antiviral cytokines but have impaired degranulation response

Abstract: The major histocompatibility complex (MHC) haplotype is one of the major determinants of genetic resistance and susceptibility of chickens to Marek’s disease (MD) which is caused by an oncogenic herpesvirus; Marek’s disease virus (MDV). To determine differential functional abilities of T cells associated with resistance and susceptibility to MD, we identified immunodominant CD4+TCRvβ1 T cell epitopes within the pp38 antigen of MDV in B19 and B21 MHC haplotype chickens using an ex vivo ELISPOT assay for chicken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…It has been reported that IFN-γ produced by activated human γδ T cells initiates a T helper type 1 (Th1) response via the induction of Th1-promoting dendritic cells (DCs) [ 30 , 31 , 32 ]. We also demonstrated an association of the induction of a potent anti-MDV Th1 response with resistance to MD [ 33 , 34 ]. Our results showing that Th1 cytokines, IFN-γ and IL-2, were upregulated and one of the anti-inflammatory cytokines, TGF-β, was downregulated in ex vivo-stimulated PBMCs with anti-TCRγδ mAb and in the spleen after the infusion of ex vivo-stimulated PBMCs at the transcript level indicate that activated chicken γδ T cells may contribute to the initiation of the Th1 response, which is shown to be important for the control of MD-lymphoma ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that IFN-γ produced by activated human γδ T cells initiates a T helper type 1 (Th1) response via the induction of Th1-promoting dendritic cells (DCs) [ 30 , 31 , 32 ]. We also demonstrated an association of the induction of a potent anti-MDV Th1 response with resistance to MD [ 33 , 34 ]. Our results showing that Th1 cytokines, IFN-γ and IL-2, were upregulated and one of the anti-inflammatory cytokines, TGF-β, was downregulated in ex vivo-stimulated PBMCs with anti-TCRγδ mAb and in the spleen after the infusion of ex vivo-stimulated PBMCs at the transcript level indicate that activated chicken γδ T cells may contribute to the initiation of the Th1 response, which is shown to be important for the control of MD-lymphoma ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…In chickens, the two T-cell lineages can be distinguished based on the types of chains they possess, which include αVβ1 and αVβ2 chains. T cells expressing αVβ1 chains from infected or vaccinated chickens, but not naïve birds, recognize peptides from avian viruses in association with classical MHC molecules ( 46 ). Thus, T cells expressing αVβ1 chains are part of adaptive immunity.…”
Section: Overview Of the Avian Immune Systemmentioning
confidence: 99%
“…Thus, T cells expressing αVβ1 chains are part of adaptive immunity. However, it remains unclear whether T cells expressing αVβ2 chains are also part of adaptive immunity, as no specific antigens recognized by this TCR have yet been identified ( 46 ). Moreover, the CD4 and CD8 co-receptors, which bind to major histocompatibility (MHC) I and MHC II, respectively, have also been identified in chickens and allow for further classification.…”
Section: Overview Of the Avian Immune Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…MDV replicates and sheds from feather follicle epithelial cells and intermediate epidermal layers of the foot skin in cell-free form into the environment [ 1 , 9 ]. Vaccination induces anti-MDV T cell responses [ 10 , 11 ], which reduce host symptoms and prolong survival, but it fails to inhibit virus replication and shedding [ 1 ]. Failure to induce sterile immunity has led to the emergence of more virulent MDV [ 12 ].…”
Section: Introductionmentioning
confidence: 99%